Automatic language identification: a case study of Pahari languages. - Gusain, Rachana; Dash, Satya Ranjan; Parida, Shantipriya; Jha, Girish Nath (Language Resources & Evaluation, 2023)
In an attempt to expand the inclusiveness of Natural Language Processing, this paper focuses on developing resources and building machine learning models to identify four languages of the Northern Indo-Aryan family, also known as Pahari languages—Nepali, Garhwali, Kumaoni, and Dogri. This is the first attempt towards building identification models for Pahari languages and developing a plain text corpus for Garhwali and Kumaoni, both of which are lesser-known and under-resourced languages/mother tongues of India. The collected corpus, including data in Nepali and Dogri, is statistically analyzed at the word level. We also trained traditional machine learning models for Pahari language identification on this corpus and found that character n-grams based Linear Support Vector Machines performed best with 99.28% accuracy.